The theatre of work - Wilkinson, Clive, ....- (Amsterdam : Frame Publishers, 2019)
An exclusive look at the inner-workings of the Los Angeles-based architectural practice Clive Wilkinson Architects, explaining an innovative approach to workplace design.
Keywords: Design